Optimized control of three-phase inverters to minimize total harmonic distortion in a grid-connected photovoltaic system - Lamreoua Abdelhak; Benslimane Anas; Bouchnaif Jamal; El Ouariachi Mostafa (Institute of Advanced Engineering and Science, 2022)
Currently, the energy transfer process to the grid of the PV system is based on the importance of less harmonics and high efficiency. The evaluation of harmonics distortion of current is based on the value of THDi (<<5%), this last becomes very high if the current leakage is high, which causes losses of the grid and safety problems. Therefore, our job is to improve the classic control method of PV inverters used to reduce grid loss and improve electricity prices. This study is a proposal toward the modelization and improvement of the three-phase two-level, and multi-level photovoltaic (PV) inverter command, using space vector, and sinusoidal control based on controlling the active and reactive current delivered into the grid indirectly with a resonant controller (PIR) for a nonlinear load (NLL). The results of the simulations obtained by the new control methodology, SPWM, and SVPWM show that its performance is better compared with the simple modulation (PWM); the total harmonic distortion (THD) of current in both methods (SVPWM) and (SPWM) is better than that obtained with conventional commands. Also, multilevel converters control produces better quality waveforms, reducing current harmonic distortion.